Hearing Words Written. Issue 3 (11th November 2016) - Kyriakides, Yannis
Abstract : Over the past few years, I have developed a form of composition – which I call music–text–film – in which I explore the dynamics between sound, words and visuals. In this article I will attempt to explain how meaning is constructed in the interplay between these layers of media. Taking as an example three of my works, Subliminal: The Lucretian Picnic, Dreams of the Blind and The Arrest, I analyse and discuss aspects of narrative, point of view, metaphor and cross-modal perception, as a way of understanding how multimedia art, specifically in the audiovisual domain, is experienced. One of the issues that arose out of these pieces was the question of location of the 'voice'. It is as if a state of limbo is created between the narrative voice of the text and the implied voice of the music, due to the absence of a conventional focal point to pin it on – an actor or a singer. I would like to suggest that because of this vacancy and the way the projected word takes the place of the sung or spoken voice, the inner voice of the audience becomes activated. This then becomes a vital immersive dimension in the performance, as the inner voice of the audience finds its place within the space of the composition.